Effect of Corporate Tax Policies on Corporate Social Responsibility (CSR) Initiatives in Nigeria - Ekwueme, Daniel (American Journal of Law, 2024)
Purpose: The aim of the study was to assess the effect of corporate tax policies on corporate social responsibility (CSR) initiatives in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that lower corporate taxes may lead to increased CSR spending as companies have more resources to allocate towards social and environmental initiatives, others argue that higher tax rates can incentivize CSR activities by encouraging companies to invest in socially responsible projects as a means to offset tax liabilities. Additionally, certain tax incentives and deductions specifically targeted at CSR expenditures can further encourage companies to engage in socially responsible behavior. However, the impact of tax policies on CSR initiatives can vary depending on factors such as industry, firm size, and the overall economic environment. Overall, understanding the interplay between corporate tax policies and CSR is crucial for policymakers and businesses aiming to promote sustainable and socially responsible practices. Implications to Theory, Practice and Policy: Stakeholder theory, agency theory and institutional theory may be used to anchor future studies on assessing effect of corporate tax policies on corporate social responsibility (CSR) initiatives in Nigeria. Corporations should enhance their transparency and disclosure practices regarding CSR expenditures, tax payments, and incentives availed. Policymakers should design tax incentives that explicitly promote responsible corporate behavior, such as tax credits or deductions for CSR expenditures.